PERANCANGAN OFFLINE COMPUTER AIDED LEARNING BERBASIS DEKSTOP - Aropatun Anisa (FT TI 16 UMY 089, 2016)
CAL is available at this time designed as a learning tool for students that can be accessed online through the LMS in the form of SCORM module. Cal is loaded with large-sized content and requires a high speed Internet that have to access it. This condition causes problems when a student does not have enough Internet connection so that students can not use CAL and lecturers can not monitor the progress of students' learning. The purpose of this research is to make dekstop cal that can be used students to learn wherever they may, without required to connect to the internet.This research use the model system development or engineering information systems sdlc (software development life cycle) consisting of the planning stages, analysis, design, implementation, testing, this approach is regular made an top-down. The results of this study the authors can create desktop CAL dapt accessed offline and return value to answer questions can be sent , it can be concluded that this desktop -based CAL can be used by the student to learn and exercises without any internet connection Keyword: Dekstop CAL, evaluation lecturers, internet connection